A systematic review of the incidence of and risk factors for postoperative atrial fibrillation following general surgery1. (4th November 2017) - Chebbout, R.; Heywood, E. G.; Drake, T. M.; Wild, J. R. L.; Lee, J.; Wilson, M.; Lee, M. J.
Summary: Atrial fibrillation is a common cardiac arrhythmia and can occur de novo following a surgical procedure. It is associated with increased inpatient and long‐term mortality. There is limited evidence concerning new‐onset atrial fibrillation following abdominal surgery. This study aimed to identify the prevalence of and risk factors for postoperative atrial fibrillation in the general surgical population. A systematic search of the Embase, MEDLINE and Cochrane (CENTRAL) databases was conducted. Studies were included in the review if they reported cases of new‐onset atrial fibrillation within 30 days of the index operation. Results were evaluated qualitatively due to substantial clinical heterogeneity. Incidence rates were pooled using a weighted random‐effects meta‐analysis model. A total of 835 records were initially identified, from which 32 full texts were retrieved. Following review, 13 studies were included that involved 52, 959 patients, of whom 10.94% (95%CI 7.22–15.33) developed atrial fibrillation. Five studies of patients undergoing oesophagectomy (n = 376/1923) had a weighted average rate of 17.66% (95%CI 12.16–21.47), compared with 7.63% (95%CI 4.39–11.98) from eight studies of non‐oesophageal surgery (n = 2927/51, 036). Identified risk factors included: increasing age; history of cardiac disease; postoperative complications, particularly, sepsis, pneumonia and pleural effusions. New‐onset postoperative atrial fibrillation is common, and is more frequent after surgery involving the thorax. Future work should focus on stratifying risk to allow targeted prophylaxis of atrial fibrillation and other peri‐operative complications.